A high-barrier degradable composite packaging material and preparation method thereof
By modifying polylactic acid and optimizing the composition distribution ratio, combined with bamboo fiber oxidation and PEG modification technology, the shortcomings of existing degradable packaging materials in terms of mechanical properties, gas barrier properties and cost are solved, and composite packaging materials with high barrier, good mechanical properties and degradability are achieved.
Patent Information
- Application Number
- CN202510026558.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-08
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-01-08
AI Technical Summary
Existing degradable packaging materials have shortcomings in terms of mechanical properties, gas barrier properties and cost, and poor compatibility of different materials leads to unstable performance.
Modified polylactic acid is used as the main component, and by optimizing the component distribution ratio and preparation methods, including bamboo fiber oxidation and PEG modification, it forms a bamboo fiber core-polyethylene glycol-polylactic acid composite structure, and combines other materials such as polyadipate-butadiene terephthalate, polycaprolactone, polyvinyl alcohol and antioxidants to improve the barrier properties and mechanical properties of the material.
It achieves high barrier properties, good mechanical properties and degradability, meets the application needs of environmentally friendly packaging materials, and improves the toughness and heat resistance of the material.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of packaging materials, and in particular to a high-barrier degradable composite packaging material and a preparation method thereof. Background Art
[0002] With the improvement of environmental awareness and the attention paid by various countries to the treatment of plastic pollution, the development and application of degradable packaging materials has become an important direction for the development of the industry. Degradable materials can be divided into natural polymer materials (such as starch and cellulose) and biodegradable synthetic materials according to their sources. Among them, biodegradable synthetic materials have broad application prospects in the packaging field due to their controllable properties and good processing properties.
[0003] At present, the common biodegradable synthetic materials on the market mainly include polybutylene adipate-terephthalate (PBAT), polylactic acid (PLA), polycaprolactone (PCL), polybutylene succinate (PBS), polyhydroxyalkanoate (PHA), etc. However, single biodegradable materials often have defects such as insufficient mechanical properties and poor gas barrier properties, which are difficult to meet actual packaging needs.
[0004] PBAT is a biodegradable material with excellent ductility and flexibility, high elongation at break, good processing performance and compatibility with other materials, but its tensile strength is low and its gas barrier performance is not ideal. Polylactic acid, as the most representative biodegradable material, has good transparency and processability, and its tensile strength can reach 50~70MPa, but it has problems of poor toughness and brittleness, and its gas barrier performance is poor due to the limitation of molecular structure. PCL has good flexibility and biocompatibility, high elongation at break, but its melting point is low, and its mechanical properties and thermal stability are poor.
[0005] PBS has good thermal stability and mechanical properties, but its cost is high and its processing window is narrow. PHA materials have excellent biodegradability, but their performance is highly dependent on the fermentation process, and they have problems such as poor thermal stability and difficulty in processing. In addition, these materials also face common problems such as high cost and unstable performance in practical applications.
[0006] In order to improve the performance of biodegradable materials, the industry usually adopts a multi-component blending modification method. For example, blending PLA with PBAT can improve the toughness of PLA, and blending PCL with PLA can improve the ductility of the material.
[0007] CN114163785A discloses a starch-based biodegradable food packaging film modified by a composite nano material and a preparation method thereof. The raw materials are composed of the following components in parts by weight: 30-40 parts of starch, 10-20 parts of PLA, 10-20 parts of PCL, 60-70 parts of PBAT, 6-10 parts of composite nano material, 0.5-1.5 parts of antioxidant, 0.5-1.5 parts of plasticizer, and 0.5-1.0 parts of lubricant.
[0008] However, the main problems currently exist are: first, the poor compatibility between different degradable materials often leads to unstable performance of composite materials; second, the addition of modifiers can easily cause the degradation performance of the material to decrease; in addition, how to ensure the degradability of the material while achieving excellent barrier properties has always been a technical difficulty in this field.
[0009] Therefore, it is of great practical significance to develop a degradable composite packaging material with good component compatibility, stable performance and excellent barrier properties. This material should not only meet the barrier performance requirements in the packaging field, but also maintain good degradability and have excellent mechanical properties and processing properties. Summary of the invention
[0010] In order to solve the shortcomings of the prior art, the purpose of the present invention is to provide a high-barrier degradable composite packaging material and a preparation method thereof. The components of the prepared composite packaging material act synergistically so that the final product has excellent barrier properties, good mechanical properties and degradability, meeting the application requirements of environmentally friendly packaging materials.
[0011] In order to achieve the above object, the present invention adopts the following technical solution:
[0012] A high-barrier biodegradable composite packaging material is made of the following components, measured by weight: 35-50 parts of polybutylene adipate-terephthalate, 50-60 parts of modified polylactic acid, 6-12 parts of polycaprolactone, 3-10 parts of polyvinyl alcohol, 3-5 parts of polyethyleneimine, 2-4 parts of glycerol, 0.5-2 parts of antioxidant, 0.5-2 parts of polyethylene wax and 0.5-2 parts of sodium pyrophosphate.
[0013] Preferably, the preparation method of the modified polylactic acid comprises the following steps:
[0014] (1) dispersing bamboo fiber powder into deionized water, adding TEMPO and NaBr, stirring evenly, cooling in an ice bath, slowly dropping NaClO solution, then adjusting the pH of the system, stirring the reaction, filtering, washing, and drying the product to obtain oxidized bamboo fiber;
[0015] Oxidation of bamboo fiber: In the redox system of NaBr and NaClO, TEMPO radicals are first oxidized by NaClO to generate nitrogen oxide ions, which then react with C6-OH of cellulose to generate aldehyde intermediates; under alkaline conditions, the aldehyde groups are further oxidized to carboxyl groups, while TEMPO is reduced to regenerate free radicals, thus achieving a catalytic cycle. This process maintains the β-1,4-glycosidic bond structure of the cellulose main chain and selectively introduces a carboxyl functional group at the C6 position.
[0016] Preferably, in step (1), the concentration of NaClO solution is 5-10wt%; the usage ratio of bamboo fiber powder, deionized water, TEMPO, NaBr, and NaClO solution is 10g:200mL:0.156-3.12g:0.515-5.15g:50-200mL.
[0017] Preferably, in step (1), the system is cooled to 0-5°C in an ice bath, and the pH of the system is adjusted to 9-11 with a NaOH solution; the stirring reaction conditions are 0-30°C for 4-24 hours, and the pH is regularly checked and adjusted in time.
[0018] (2) Dispersing the oxidized bamboo fiber in DMF, adding EDC and NHS, stirring at room temperature for activation, then adding PEG200 DMF solution, stirring for reaction under nitrogen atmosphere, distilling the product under reduced pressure, washing, and drying to obtain PEG-modified bamboo fiber;
[0019] Surface modification of PEG: EDC first reacts with the carboxyl group of oxidized cellulose to form an O-acylurea intermediate, which is unstable and prone to rearrangement; NHS reacts with it to form an active ester intermediate, which is more stable and has higher reactivity. Subsequently, the hydroxyl group of PEG200 attacks the acyl carbon of the active ester intermediate, undergoes an ester exchange reaction, forms an ester bond, and releases NHS at the same time. This process achieves the covalent grafting of PEG200 on the cellulose surface.
[0020] Preferably, in step (2), the usage ratio of oxidized bamboo fiber, DMF, EDC, NHS, and DMF solution of PEG200 is 10 g:100 mL:1.91-9.55 g:1.15-5.75 g:50 mL; and the content of PEG200 in the DMF solution of PEG200 is 5-30 g / 50 mL.
[0021] Preferably, in step (2), the activation is carried out by stirring at room temperature for 10 to 30 minutes; the stirring reaction conditions are 20 to 60° C. and the stirring reaction is carried out for 12 to 36 hours; and the product is washed three times with ethanol and deionized water respectively.
[0022] (3) The PEG-modified bamboo fiber is dispersed in toluene, and lactide monomer and stannous octoate are added. The mixture is refluxed under a nitrogen atmosphere. The product is filtered, washed, and dried to obtain modified polylactic acid.
[0023] In-situ polymerization of lactide: Stannous octoate and the hydroxyl group at the end of PEG first form an active center, and then the acyl oxygen of the lactide monomer is attacked by nucleophilicity, resulting in the rupture of the ester bond and the opening of the ring, exposing a new hydroxyl end to continue to initiate polymerization. This coordination-insertion mechanism allows the polymer chain to grow outward from the fiber surface, eventually forming a composite material with bamboo fiber as the core and PLA as the periphery.
[0024] Preferably, in step (3), the usage ratio of PEG-modified bamboo fiber, toluene, lactide, and stannous octoate is 10 g:100 mL:10-50 g:0.01-0.5 g.
[0025] Preferably, in step (3), the reflux reaction conditions are reflux reaction at 120-140° C. for 12-36 hours; and the product is washed three times with dichloromethane.
[0026] The present invention also claims protection for a method for preparing the high-barrier degradable composite packaging material, comprising the following steps: mixing the raw materials in parts by weight to obtain a mixture, transferring the mixture to a twin-screw extruder, extruding and granulating to obtain a blended masterbatch, blow-molding the blended masterbatch into a film, and naturally cooling to obtain the high-barrier degradable composite packaging material.
[0027] Preferably, the screw temperature is set to 160-180°C and the nozzle temperature is set to 180-185°C.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] 1. The present invention provides a high-barrier degradable composite packaging material, which achieves excellent comprehensive performance by optimizing the component ratio: modified polylactic acid provides excellent mechanical strength and toughness through the bamboo fiber core-polyethylene glycol-polylactic acid composite structure design; polyadipate-butylene terephthalate provides good toughness and processing performance; polycaprolactone enhances the flexibility of the material; polyvinyl alcohol and polyethyleneimine form an interpenetrating network structure, which significantly improves the oxygen barrier property; glycerol is used as a plasticizer to improve the processing performance; antioxidants and sodium pyrophosphate provide thermal stability; polyethylene wax improves the demoulding performance during molding. The synergistic effect of each component makes the final product have excellent barrier properties, good mechanical properties and degradability, meeting the application requirements of environmentally friendly packaging materials.
[0030] 2. The present invention provides a modified polylactic acid, which achieves significant performance improvement by selecting bamboo fiber as a substrate and adopting a three-step chemical modification strategy. As a renewable natural fiber, bamboo fiber not only has excellent mechanical strength and environmentally friendly properties, but its unique fiber structure can be used as a reinforcing phase of composite materials, and the abundant hydroxyl groups on the surface also provide sufficient active sites for chemical modification. The bamboo fiber was selectively modified by the TEMPO / NaBr / NaClO oxidation system to achieve the conversion of the C6 hydroxyl group to the carboxyl group, while maintaining the integrity of the cellulose main chain, providing uniformly distributed reaction sites for subsequent modification. The EDC / NHS activation system was used to achieve efficient grafting of PEG200. The introduced PEG200 as a flexible chain segment significantly improved the toughness of the material, while increasing the surface affinity of the bamboo fiber and improving its dispersibility in the matrix. Its terminal hydroxyl group can also be used as an initiation point for ring-opening polymerization. Finally, stannous octoate was used as a catalyst for in-situ polymerization of lactide, and a polylactic acid molecular chain with PEG as a connecting bridge was constructed on the surface of bamboo fiber, forming a unique structure of bamboo fiber core-polyethylene glycol bridge-polylactic acid shell, and realizing a strong interface bonding between bamboo fiber and polylactic acid matrix. The modified bamboo fiber forms an intricate microstructure in the matrix, which significantly increases the water vapor permeation path and improves the barrier properties of the material; at the same time, the introduction of PEG flexible chain segments and the uniform dispersion of bamboo fibers effectively improve the toughness and heat stability of polylactic acid and improve its plasticity. This step-by-step modification strategy ultimately obtains modified polylactic acid with high interface bonding strength, excellent mechanical properties, good thermal stability, improved processing performance, and good biodegradability, providing a new technical path for the development of high-performance degradable packaging materials. DETAILED DESCRIPTION
[0031] In order to make the purpose, technical solution and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with embodiments. Of course, the specific embodiments described here are only used to explain the present invention and are not used to limit the present invention.
[0032] Unless otherwise specified, the chemical reagents and materials in the present invention are purchased from commercial sources or synthesized from raw materials purchased from commercial sources.
[0033] Bamboo fiber powder, 400-1000 mesh, purchased from Jiangxi Polysilicon Mining Co., Ltd.;
[0034] PBAT was purchased from Kanghui New Material Technology Co., Ltd., with a number average molecular weight > 100 and a melt index of 3~10g / 10min;
[0035] The weight-average molecular weight of PCL is between 60,000 and 120,000 and was purchased from National Energy Technology Company, model GN5066;
[0036] Polyvinyl alcohol is PVA100-27 provided by Sinopec, with a brand number of 1799;
[0037] Polyethyleneimine was purchased from Shandong Dengnuo Chemical Co., Ltd., model PEI;
[0038] Polyethylene wax was purchased from Shanghai Panren International Trade Co., Ltd. with a molecular weight of 1500-5000 and model number H116.
[0039] A method for preparing a high-barrier degradable composite packaging material comprises the following steps:
[0040] (1) Disperse 10 g of bamboo fiber powder into 200 mL of deionized water, add 0.156-3.12 g of TEMPO and 0.515-5.15 g of NaBr, stir evenly, cool the system to 0-5 °C in an ice bath, slowly drop 50-200 mL of 5-10 wt% NaClO solution, then adjust the pH of the system to 9-11 with NaOH solution, stir the reaction at 0-30 °C for 4-24 h, regularly check the pH and adjust it in time, filter, wash and dry the product to obtain oxidized bamboo fiber;
[0041] (2) Disperse 10 g of oxidized bamboo fiber in 100 mL of DMF, add 1.91-9.55 g of EDC and 1.15-5.75 g of NHS, and activate by stirring at room temperature for 10-30 min. Then add 50 mL of DMF solution of PEG200 (the content of PEG200 is 5-30 g / 50 mL), and stir the reaction at 20-60 °C under nitrogen atmosphere for 12-36 h. Distill the product under reduced pressure, wash it with ethanol and deionized water three times respectively, and dry it in vacuum to obtain PEG-modified bamboo fiber.
[0042] (3) Disperse 10 g of PEG-modified bamboo fiber in 100 mL of toluene, add 10-50 g of lactide monomer and 0.01-0.5 g of stannous octoate, reflux for 12-36 h at 120-140 °C in a nitrogen atmosphere, filter the product, wash it with dichloromethane three times, and vacuum dry it to obtain modified polylactic acid;
[0043] (4) 35-50 parts of polybutylene adipate-terephthalate, 50-60 parts of modified polylactic acid, 6-12 parts of polycaprolactone, 3-10 parts of polyvinyl alcohol, 3-5 parts of polyethyleneimine, 2-4 parts of glycerol, 0.5-2 parts of antioxidant, 0.5-2 parts of polyethylene wax and 0.5-2 parts of sodium pyrophosphate are mixed to obtain a mixture, and the mixture is transferred to a twin-screw extruder, and the screw temperature is set to 160-180°C and the nozzle temperature is set to 180-185°C. Extrusion granulation is performed to obtain a blended masterbatch, and the blended masterbatch is blown into a film, and naturally cooled to obtain the high barrier biodegradable composite packaging material.
[0044] The present invention will be further described below through specific embodiments.
[0045] Example 1
[0046] A method for preparing a high-barrier degradable composite packaging material comprises the following steps:
[0047] (1) Disperse 10 g of bamboo fiber powder into 200 mL of deionized water, add 3.12 g of TEMPO and 5.15 g of NaBr, stir evenly, cool the system to 5 ° C in an ice bath, slowly drop 200 mL of 5 wt% NaClO solution, then adjust the pH of the system to 11 with NaOH solution, stir and react at 30 ° C for 4 h, regularly check the pH and adjust it in time, filter, wash and dry the product to obtain oxidized bamboo fiber;
[0048] (2) Disperse 10 g of oxidized bamboo fiber in 100 mL of DMF, add 9.55 g of EDC and 5.75 g of NHS, and stir at room temperature for activation for 30 min. Then add 50 mL of PEG200 DMF solution (the content of PEG200 is 30 g / 50 mL), stir and react at 60 °C under nitrogen atmosphere for 12 h, distill the product under reduced pressure, wash it with ethanol and deionized water for 3 times respectively, and dry it in vacuum to obtain PEG-modified bamboo fiber.
[0049] (3) Disperse 10 g of PEG-modified bamboo fiber in 100 mL of toluene, add 50 g of lactide monomer and 0.5 g of stannous octoate, reflux for 12 h at 140 °C in a nitrogen atmosphere, filter the product, wash it with dichloromethane three times, and vacuum dry it to obtain modified polylactic acid;
[0050] (4) 500 g of polybutylene adipate-terephthalate, 600 g of modified polylactic acid, 120 g of polycaprolactone, 100 g of polyvinyl alcohol, 50 g of polyethyleneimine, 40 g of glycerol, 20 g of antioxidant 1010, 20 g of polyethylene wax and 20 g of sodium pyrophosphate were mixed to obtain a mixture, and the mixture was transferred to a twin-screw extruder, the screw temperature was set to 170°C and the nozzle temperature was set to 182°C, and granulated by extrusion to obtain a blended masterbatch, and the blended masterbatch was blown into a film, and naturally cooled to obtain the high barrier degradable composite packaging material.
[0051] Example 2
[0052] A method for preparing a high-barrier degradable composite packaging material comprises the following steps:
[0053] (1) Disperse 10 g of bamboo fiber powder into 200 mL of deionized water, add 2.13 g of TEMPO and 3.6 g of NaBr, stir evenly, cool the system to 4 ° C in an ice bath, slowly drop 150 mL of 5 wt% NaClO solution, then adjust the pH of the system to 10 with NaOH solution, stir and react at 20 ° C for 10 h, regularly check the pH and adjust it in time, filter, wash and dry the product to obtain oxidized bamboo fiber;
[0054] (2) Disperse 10 g of oxidized bamboo fiber in 100 mL of DMF, add 7 g of EDC and 3.88 g of NHS, stir and activate at room temperature for 20 min, then add 50 mL of PEG200 DMF solution (the content of PEG200 is 20 g / 50 mL), stir and react at 50 °C under nitrogen atmosphere for 20 h, distill the product under reduced pressure, wash it with ethanol and deionized water for 3 times respectively, and dry it in vacuum to obtain PEG-modified bamboo fiber;
[0055] (3) Disperse 10 g of PEG-modified bamboo fiber in 100 mL of toluene, add 40 g of lactide monomer and 0.4 g of stannous octoate, reflux for 20 h at 130 °C in a nitrogen atmosphere, filter the product, wash it with dichloromethane three times, and vacuum dry it to obtain modified polylactic acid;
[0056] (4) 450 g of polybutylene adipate-terephthalate, 560 g of modified polylactic acid, 100 g of polycaprolactone, 80 g of polyvinyl alcohol, 40 g of polyethyleneimine, 35 g of glycerol, 15 g of antioxidant 1010, 15 g of polyethylene wax and 15 g of sodium pyrophosphate were mixed to obtain a mixture, and the mixture was transferred to a twin-screw extruder, the screw temperature was set to 170° C., the nozzle temperature was set to 182° C., and granulation was performed by extrusion to obtain a blended masterbatch, the blended masterbatch was blown into a film, and naturally cooled to obtain the high barrier degradable composite packaging material.
[0057] Example 3
[0058] A method for preparing a high-barrier degradable composite packaging material comprises the following steps:
[0059] (1) Disperse 10 g of bamboo fiber powder into 200 mL of deionized water, add 1.15 g of TEMPO and 2.07 g of NaBr, stir evenly, cool the system to 2 ° C in an ice bath, slowly drop 100 mL of 10 wt% NaClO solution, then adjust the pH of the system to 10 with NaOH solution, stir and react at 10 ° C for 16 h, regularly check the pH and adjust it in time, filter, wash and dry the product to obtain oxidized bamboo fiber;
[0060] (2) Disperse 10 g of oxidized bamboo fiber in 100 mL of DMF, add 4.41 g of EDC and 2.68 g of NHS, stir and activate at room temperature for 20 min, then add 50 mL of PEG200 DMF solution (the content of PEG200 is 10 g / 50 mL), stir and react at 40 °C under nitrogen atmosphere for 28 h, distill the product under reduced pressure, wash it with ethanol and deionized water for 3 times respectively, and dry it in vacuum to obtain PEG-modified bamboo fiber;
[0061] (3) Disperse 10 g of PEG-modified bamboo fiber in 100 mL of toluene, add 20 g of lactide monomer and 0.2 g of stannous octoate, reflux for 28 h at 130 °C in a nitrogen atmosphere, filter the product, wash it three times with dichloromethane, and vacuum dry it to obtain modified polylactic acid;
[0062] (4) 400 g of polybutylene adipate-terephthalate, 540 g of modified polylactic acid, 80 g of polycaprolactone, 50 g of polyvinyl alcohol, 40 g of polyethyleneimine, 25 g of glycerol, 10 g of antioxidant 1010, 10 g of polyethylene wax and 10 g of sodium pyrophosphate were mixed to obtain a mixture, and the mixture was transferred to a twin-screw extruder, and the screw temperature was set to 170° C. and the nozzle temperature was set to 182° C., and granulated by extrusion to obtain a blended masterbatch, and the blended masterbatch was blown into a film, and naturally cooled to obtain the high barrier degradable composite packaging material.
[0063] Example 4
[0064] A method for preparing a high-barrier degradable composite packaging material comprises the following steps:
[0065] (1) Disperse 10 g of bamboo fiber powder into 200 mL of deionized water, add 0.156 g of TEMPO and 0.515 g of NaBr, stir evenly, cool the system to 0 ° C in an ice bath, slowly drop 50 mL of 5 wt% NaClO solution, then adjust the pH of the system to 9 with NaOH solution, stir and react at 0 ° C for 24 h, regularly check the pH and adjust it in time, filter, wash and dry the product to obtain oxidized bamboo fiber;
[0066] (2) Disperse 10 g of oxidized bamboo fiber in 100 mL of DMF, add 1.91 g of EDC and 1.15 g of NHS, stir and activate at room temperature for 10 min, then add 50 mL of PEG200 DMF solution (the content of PEG200 is 5 g / 50 mL), stir and react at 20 °C under nitrogen atmosphere for 12 h, distill the product under reduced pressure, wash it with ethanol and deionized water for 3 times respectively, and dry it in vacuum to obtain PEG-modified bamboo fiber;
[0067] (3) Disperse 10 g of PEG-modified bamboo fiber in 100 mL of toluene, add 10 g of lactide monomer and 0.01 g of stannous octoate, reflux for 36 h at 120 °C in a nitrogen atmosphere, filter the product, wash it three times with dichloromethane, and vacuum dry it to obtain modified polylactic acid;
[0068] (4) 350 g of polybutylene adipate-terephthalate, 500 g of modified polylactic acid, 60 g of polycaprolactone, 30 g of polyvinyl alcohol, 30 g of polyethyleneimine, 20 g of glycerol, 5 g of antioxidant 1010, 5 g of polyethylene wax and 5 g of sodium pyrophosphate were mixed to obtain a mixture, and the mixture was transferred to a twin-screw extruder, the screw temperature was set to 170°C and the nozzle temperature was set to 182°C, and granulated by extrusion to obtain a blended masterbatch, and the blended masterbatch was blown into a film, and naturally cooled to obtain the high barrier degradable composite packaging material.
[0069] Comparative Example 1
[0070] A method for preparing a composite packaging material comprises the following steps:
[0071] (1) Disperse 10 g of bamboo fiber powder into 200 mL of deionized water, add 3.12 g of TEMPO and 5.15 g of NaBr, stir evenly, cool the system to 5 ° C in an ice bath, slowly drop 200 mL of 5 wt% NaClO solution, then adjust the pH of the system to 11 with NaOH solution, stir and react at 30 ° C for 4 h, regularly check the pH and adjust it in time, filter, wash and dry the product to obtain oxidized bamboo fiber;
[0072] (2) Disperse 10 g of oxidized bamboo fiber in 100 mL of DMF, add 9.55 g of EDC and 5.75 g of NHS, and stir at room temperature for activation for 30 min. Then add 50 mL of PEG200 DMF solution (the content of PEG200 is 30 g / 50 mL), stir and react at 60 °C under nitrogen atmosphere for 12 h, distill the product under reduced pressure, wash it with ethanol and deionized water for 3 times respectively, and dry it in vacuum to obtain PEG-modified bamboo fiber.
[0073] (3) 500 g of polybutylene adipate-terephthalate, 500 g of polylactic acid, 100 g of PEG-modified bamboo fiber, 120 g of polycaprolactone, 100 g of polyvinyl alcohol, 50 g of polyethyleneimine, 40 g of glycerol, 20 g of antioxidant 1010, 20 g of polyethylene wax, and 20 g of sodium pyrophosphate were mixed to obtain a mixture, and the mixture was transferred to a twin-screw extruder, the screw temperature was set to 170° C., the nozzle temperature was set to 182° C., and granulation was performed by extrusion to obtain a blended masterbatch, the blended masterbatch was blown into a film, and naturally cooled to obtain the high barrier degradable composite packaging material.
[0074] Comparative Example 2
[0075] A method for preparing a composite packaging material comprises the following steps:
[0076] (1) Disperse 10 g of bamboo fiber powder into 200 mL of deionized water, add 3.12 g of TEMPO and 5.15 g of NaBr, stir evenly, cool the system to 5 ° C in an ice bath, slowly drop 200 mL of 5 wt% NaClO solution, then adjust the pH of the system to 11 with NaOH solution, stir and react at 30 ° C for 4 h, regularly check the pH and adjust it in time, filter, wash and dry the product to obtain oxidized bamboo fiber;
[0077] (2) 500 g of polybutylene adipate-terephthalate, 500 g of polylactic acid, 100 g of oxidized bamboo fiber, 120 g of polycaprolactone, 100 g of polyvinyl alcohol, 50 g of polyethyleneimine, 40 g of glycerol, 20 g of antioxidant 1010, 20 g of polyethylene wax, and 20 g of sodium pyrophosphate are mixed to obtain a mixture, and the mixture is transferred to a twin-screw extruder, and the screw temperature and the nozzle temperature are set to 170° C. and 182° C., and extruded and granulated to obtain a blended masterbatch, and the blended masterbatch is blown into a film, and naturally cooled to obtain the composite packaging material.
[0078] Comparative Example 3
[0079] A method for preparing a composite packaging material comprises the following steps:
[0080] 500 g of polybutylene adipate-terephthalate, 600 g of polylactic acid, 120 g of polycaprolactone, 100 g of polyvinyl alcohol, 50 g of polyethyleneimine, 40 g of glycerol, 20 g of antioxidant 1010, 20 g of polyethylene wax, and 20 g of sodium pyrophosphate are mixed to obtain a mixture, and the mixture is transferred to a twin-screw extruder, the screw temperature is set to 170° C., the nozzle temperature is set to 182° C., and granulation is performed by extrusion to obtain a blended masterbatch, the blended masterbatch is blown into a film, and naturally cooled to obtain the composite packaging material.
[0081] The composite packaging materials prepared in Examples 1 to 4 and Comparative Examples 1 to 3 were subjected to performance tests, and the tensile strength and elongation at break were tested with reference to GB / T1040.3-2006 "Determination of tensile properties of plastics Part 3: Test conditions for films and sheets"; the impact strength was tested with reference to GB / T 9639.1-2008 "Test method for impact resistance of plastic films and sheets - free-falling dart method - Part 1: ladder method"; the oxygen permeability was tested with reference to GB / T 19789-2021 "Test method for oxygen permeability of plastic films and sheets for packaging materials - coulometer detection method"; the water vapor permeability was tested with reference to GB / T 1037-2021 "Determination of water vapor permeability of plastic films and sheets - cup weight gain and weight loss method"; and the biodegradability was tested with reference to GB / T 17603-2017 "Test method for outdoor exposure of photodegradable plastics". Specific data are shown in Table 1.
[0082] Table 1 Composite packaging material performance test results
[0083]
[0084] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A high barrier degradable composite packaging material, characterized in that: The invention is prepared from the following components by weight: 35-50 parts of polybutylene adipate-terephthalate, 50-60 parts of modified polylactic acid, 6-12 parts of polycaprolactone, 3-10 parts of polyvinyl alcohol, 3-5 parts of polyethyleneimine, 2-4 parts of glycerol, 0.5-2 parts of antioxidant, 0.5-2 parts of polyethylene wax and 0.5-2 parts of sodium pyrophosphate; The preparation method of the modified polylactic acid comprises the following steps: (1) dispersing bamboo fiber powder into deionized water, adding TEMPO and NaBr, stirring evenly, cooling in an ice bath, slowly dropping NaClO solution, then adjusting the pH of the system, stirring the reaction, filtering, washing, and drying the product to obtain oxidized bamboo fiber; (2) Dispersing the oxidized bamboo fiber in DMF, adding EDC and NHS, stirring at room temperature for activation, then adding PEG200 DMF solution, stirring for reaction under nitrogen atmosphere, distilling the product under reduced pressure, washing, and drying to obtain PEG-modified bamboo fiber; (3) The PEG-modified bamboo fiber is dispersed in toluene, and lactide monomer and stannous octoate are added. The mixture is refluxed under a nitrogen atmosphere. The product is filtered, washed, and dried to obtain modified polylactic acid.
2. The high barrier degradable composite packaging material according to claim 1, characterized in that: In step (1), the concentration of NaClO solution is 5-10wt%; the dosage ratio of bamboo fiber powder, deionized water, TEMPO, NaBr, and NaClO solution is 10g:200mL:0.156-3.12g:0.515-5.15g:50-200mL.
3. The high barrier degradable composite packaging material according to claim 1, characterized in that: In step (1), the system is cooled to 0-5°C in an ice bath, and the pH of the system is adjusted to 9-11 with a NaOH solution; the stirring reaction conditions are 0-30°C for 4-24 hours, and the pH is regularly checked and adjusted in time.
4. The high barrier degradable composite packaging material according to claim 1, characterized in that: In step (2), the usage ratio of oxidized bamboo fiber, DMF, EDC, NHS, and DMF solution of PEG200 is 10 g:100 mL:1.91-9.55 g:1.15-5.75 g:50 mL; and the content of PEG200 in the DMF solution of PEG200 is 5-30 g / 50 mL.
5. The high barrier degradable composite packaging material according to claim 1, characterized in that: In step (2), the activation is carried out by stirring at room temperature for 10 to 30 minutes; the stirring reaction conditions are 20 to 60° C. and the stirring reaction is carried out for 12 to 36 hours; and the product is washed three times with ethanol and deionized water respectively.
6. The high barrier degradable composite packaging material according to claim 1, characterized in that: In step (3), the dosage ratio of PEG-modified bamboo fiber, toluene, lactide, and stannous octoate is 10 g:100 mL:10-50 g:0.01-0.5 g.
7. The high barrier degradable composite packaging material according to claim 1, characterized in that: In step (3), the reflux reaction conditions are reflux reaction at 120-140° C. for 12-36 hours; and the product is washed three times with dichloromethane.
8. A method for preparing the high barrier degradable composite packaging material according to any one of claims 1 to 7, characterized in that: The method comprises the following steps: mixing the raw materials by weight to obtain a mixture, transferring the mixture to a twin-screw extruder, extruding and granulating to obtain a blended masterbatch, blowing the blended masterbatch into a film, and naturally cooling to obtain the high-barrier degradable composite packaging material.
9. The preparation method according to claim 8, characterized in that: Set the screw temperature to 160~180℃ and the nozzle temperature to 180~185℃.
Citation Information
Patent Citations
Blended composite material prepared from lactide surface grafted bamboo powder and polylactic acid, and preparation method and applications thereof
CN105131542A
Bamboo fiber-contained non-woven fabrics containing rose essential oil capable of continuously releasing negative oxygen ion and preparation method thereof
CN106087250A